Assessing physiological and behavioural energetics as biomarkers of environmental change in seabirds - Sorenson, Graham (University of Windsor, 2016)
Environmental change is occurring at an unprecedented rate, making traditional demographic monitoring techniques less practical and giving rise to more proactive monitoring methods. Although many ‘biomarkers’ such as physiology and behaviour are used in field research, testing their effectiveness as indicators of environmental change across multiple biological scales is key to using these tools confidently. In Chapter 2, I use a phylogenetically-controlled meta-analysis across seabird species to demonstrate the strength of the relationship between baseline corticosterone and common fitness-related traits. I found food availability and reproductive success to have strong negative relationships with corticosterone. In Chapter 3, I use an integrative approach (physiology, foraging behaviour, energetic expenditure) across multiple biological scales within a natural environmental ‘experiment’ to determine the relative sensitivity of key traits to sea ice changes in an Arctic seabird, the thick-billed murre (Uria lomvia). I found corticosterone and non-esterified fatty acids were higher and foraging strategy consisted of more frequent, short foraging trips during the low ice year. However, average daily foraging distance, estimated daily energetic expenditure, triglycerides, and beta-hydroxybutyrate remained constant across years. In the face of environmental change the birds appear to be working harder, but maintaining energy intake and energetic expenditure. Overall, my thesis serves as a model for biomarker validation and answers questions about physiological and behavioural environmental responses and fitness outcomes across seabirds.